2021
DOI: 10.1021/acs.jpclett.1c00177
|View full text |Cite
|
Sign up to set email alerts
|

BaZrS3 Chalcogenide Perovskite Thin Films by H2S Sulfurization of Oxide Precursors

Abstract: The earth-abundant ternary compound BaZrS3, which crystallizes in the perovskite-type structure, has come into view as a promising candidate for photovoltaic applications. We present the synthesis and characterization of polycrystalline perovskite-type BaZrS3 thin films. BaZrO3 precursor layers were deposited by pulsed laser deposition and sulfurized at various temperatures in an argon-diluted H2S atmosphere. We observe increasing incorporation of sulfur for higher annealing temperatures, accompanied by a red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 22 publications
4
63
0
Order By: Relevance
“…[ 42 ] Marquez et al confirmed that there is indeed no crystalline solid solution, but they also saw the gradual shift in optical absorption edge for partly sulfurized BaZrO 3 , see Figure a,b. [ 130 ] They reconciled these seemingly contradicting results by postulating the existence of an amorphous BaZr(O,S) 3 phase. Computationally, Vonrüti et al.…”
Section: The Discovered Chalcogenide Perovskitesmentioning
confidence: 98%
See 4 more Smart Citations
“…[ 42 ] Marquez et al confirmed that there is indeed no crystalline solid solution, but they also saw the gradual shift in optical absorption edge for partly sulfurized BaZrO 3 , see Figure a,b. [ 130 ] They reconciled these seemingly contradicting results by postulating the existence of an amorphous BaZr(O,S) 3 phase. Computationally, Vonrüti et al.…”
Section: The Discovered Chalcogenide Perovskitesmentioning
confidence: 98%
“…Reproduced with permission. [ 130 ] Copyright 2021, American Chemical Society. c) Ellipsometry data for Ba(Ti,Zr)S 3 and BaZr(S,Se) 3 alloys, extracted bandgaps are indicated by the solid circles.…”
Section: The Discovered Chalcogenide Perovskitesmentioning
confidence: 99%
See 3 more Smart Citations